Moral and Social Values in Evidence-Informed Deliberative Processes for Health Benefit Package Design; Comment on "Evidence-Informed Deliberative Processes for Health Benefit Package Design - Part II: A Practical Guide" - Michael J. DiStefano (Kerman University of Medical Sciences, 2023)
An evidence-informed deliberative process (EDP) is defined as "a practical and stepwise approach for health technology assessment (HTA) bodies to enhance legitimate health benefit package design based on deliberation between stakeholders to identify, reflect and learn about the meaning and importance of values, informed by evidence on these values." In this commentary, I discuss some considerations for EDPs that arise from acknowledging the difference between social and moral values. First, the best practices for implementing EDPs may differ depending on whether the approach is grounded in moral versus social values. Second, the goals of deliberation may differ when focused on moral versus social values. I conclude by offering some considerations for future research to support the use of EDPs in practice, including the need to assess how different approaches to appraisal (eg, more quantitative versus qualitative) impact perceptions of the value of deliberation itself.